Association of angiotensin converting enzyme and angiotensin II type 1 receptor genotypes with left ventricular function and mass in patients with angiographically normal coronary arteries. Issue 6 (June 1997) - Hamon, M.; Amant, C.; Bauters, C.; Richard, F.; Helbecque, N.; McFadden, E.; Lablanche, J. M.; Bertrand, M.; Amouyel, P.
Abstract : OBJECTIVE: To analyse the potential association of the angiotensin converting enzyme (ACE) and angiotensin II type 1 receptor (AT1R) gene polymorphisms on left ventricular function and mass in patients with normal coronary arteries. DESIGN: Consecutive sample. SETTING: University hospital. SUBJECTS: 141 consecutive white patients referred for coronary angiography and with angiographically normal coronary arteries. Patients with valvar diseases, cardiomyopathies, or a history of myocardial infarction were excluded. MAIN OUTCOME MEASURES: Left ventricular variables were measured for all patients. The ACE and AT1R genotypes were determined with a polymerase chain reaction based protocol using DNA prepared from white blood cells. A general linear model was used to compare data according to the ACE and to the AT1R genotypes. RESULTS: A strong association was observed between left ventricular mass and systemic hypertension (mean (SD) hypertension: 114 (31) g/m2; no hypertension 98 (23) g/m2; P < 0.003). However, no influence of ACE and AT1R polymorphisms on left ventricular mass was found, regardless of systemic hypertension. The subjects homozygous for the AT1R CC mutation had a significantly lower ejection fraction than those with allele A (AC+AA) (mean (SD) 62(12)% and 68(10)%, respectively, P < 0.05). No synergistic interaction of ACE and AT1R gene polymorphisms on left ventricular function and mass was found. CONCLUSIONS: These data do not support an association of the ACE and AT1R genotypes on left ventricular hypertrophy in white patients with normal coronary arteries.